FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE - Aldini, Vega; Solikah, Mar’atus; Sugeng (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this study is to determine the effect of leverage, profitability, company life and good corporate governance on tax avoidance in mining sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. This research uses a quantitative approach with comparative causal techniques. The samples used by the study were 21 companies and analyzed using multiple linear regression with SPSS software version 23. The results of this study are (1) the significance level of 0.749>0.005 means that partial leverage does not have a significant effect on tax avoidance. (2) the significance level of 0.019<0.005 profitability partially affects tax avoidance.(3) the significance level of 0.217>0.005 means that the life of the company partially has no significant effect on tax avoidance. (4) a significance level of 0.001<0.005 means good corporate governance. Simultaneously, leverage, profitability, company life, and good corporate governance affect tax avoidance. Researchers use the latest data, namely the 2019-2021 period.